Running on fumes: an analysis of fine particulate matter's impact on finish times in nine major US marathons, 2003-2019 - Fleury, E. S.; Bittker, G. S.; Just, A. C.; Braun, J. M. (Sports Medicine, 2025)
Background: Under controlled conditions and in some observational studies of runners, airborne fine particulate matter smaller than 2.5 microns in diameter (PM2.5) is associated with exercise performance decrements.